Structure and Functional Diversity of Surface Bacterioplankton Communities in an Overwintering Habitat for Large Yellow Croaker, Pseudosciaena crocea, of the Southern East China Sea - Yang, Wen; Zheng, Shi-Zhan; Zhou, Shou-Heng; Zhao, Li; Zhu, Jin-Yong; Lukwambe, Betina; Nicholaus, Regan; Li, Cheng-Hua; Zheng, Zhong-Ming (Frontiers in Marine Science, 2020)
Given the biogeochemical functions of marine microbes, the structure and functional diversity of bacterioplankton communities could be regarded as bioindicators that reflect environmental quality. The habitat of the large yellow croaker (Pseudosciaena crocea) is suffering from widespread degradation, but the study of croaker habitat is still insufficient. Here, we used 16S rRNA gene sequencing and functional prediction to investigate the surface bacterioplankton communities in an overwintering ground of P. crocea during the overwintering period (November 2018 to April 2019). Our results showed that the taxa and functions of the environmental bacterioplankton community exhibited obvious seasonality. Specifically, the bacterioplankton communities in autumn were characterized by animal parasites or symbionts, such as Acinetobacter baumannii and Moraxella, while organic substance-degrading bacteria, such as Rhodococcus, Stenotrophomonas and Alcanivorax, dominated in spring. Moreover, phylogenetic-based mean nearest taxon distance (MNTD) analyses indicated that dispersal limitation was the most important process governing the spatiotemporal assembly of the bacterioplankton communities. The distance decay of similarity also suggested the impact of dispersal limitation on the generation of biogeographical patterns. Furthermore, variation partitioning analysis and a partial Mantel test revealed that environmental filters, such as nutrients, temperature and salinity, had relatively weak deterministic effects on the bacterioplankton community assembly. Overall, these findings provide a basis for understanding the theory of surface microbial community assembly in the overwintering habitat of the large yellow croaker.